Visual field defects due to optic disk drusen in children - Noval, Susana; Visa, Josep; Contreras, Inés (Graefe's archive for clinical and experimental ophthalmology, 2013)
Background Optic nerve head drusen (ONHD) are deposits due to abnormalities in axonal metabolism and degeneration. Studies so far have focused on adults. Our aim was to study the effect of ONHD on visual function as well as optic nerve head structure using optical coherence tomography (OCT) in children. Methods Subjects younger than 18 years of age with ONHD and who had a reliable visual field defect in at least one eye due to ONHD were considered for inclusion. All subjects underwent an extensive ophthalmic examination including best-corrected visual acuity (BCVA), funduscopy, and SITA 24–2 standard automated perimetry. OCT scanning was performed using Cirrus-HD Model 4000. Retinal nerve fiber layer (RNFL) thickness data were compared with a group of age-matched healthy children. Results Fifteen children were included, with a mean age of 13 years (range 7 to 17 years). BCVA was 1.0 in all eyes, except in a child with concomitant esotropia. ONHD were bilateral in 13 children. Among the 28 eyes with ONHD, 12 (43 %) were classified as type 1 (buried), eight (29 %) as type 2 (ringed) and eight (29 %) as type 3 (superficial). All children had a visual field defect in at least one eye, according to the inclusion criteria; however, two eyes (7 %) had no defect in spite of the presence of ONHD. Five eyes showed an isolated enlarged blind spot (18 %), 15 cases showed a nasal defect (54 %), and six eyes showed a constricted visual field (21 %). RNFL thickness was higher in type 1 and 2 ONHD than in the control group, although these differences were only significant for the average, superior, and inferior quadrant thicknesses in type 1 and the inferior quadrant in type 2. RNFL thickness was lower in type 3 ONHD than in the control group, although these differences were only significant for the average, superior, and nasal quadrant thicknesses. Conclusions ONHD may lead to the development of visual field defects, even in children. In initial stages, ONHD produce an increase in RNFL thickness as measured with OCT. As drusen develop and become superficial, the RNFL thickness decreases. The temporal quadrant is often undamaged, probably reflecting the preservation of central visual acuity.